The Effect of Hidden Quality Cost on Supply Chain Management of Sales and Market Share - Mohamed K. Hameed; Thamer Kadhim Al-abedi; Zeina khdier abass (International Journal of Supply Chain Management, 2019)
There have been difficulties in managing costs effectively which have led to reduction in both market and sales share. This study aimed to find remedies to the challenge of determining and measuring the hidden quality costs due to its negative effect on the customer satisfaction. This study engaged in the measurement and calculation of hidden quality costs in a sound and scientific manner in order to find solutions to the problem and achieve the research objectives. Increase in the sales and profits and market share of the economic unit and satisfaction of the customer are achieved through the effective the management of these costs. A deductive approach was employed in the study and a number of conclusions were made from the analysis of the results. First, the study conclude that lack of information as provided by the total quality costs is experienced due to failure to calculate the hidden quality costs. As the hidden quality costs provide indicators, they must be applied as required. Also, there is a task related to the risks surrounding the economic growth when it comes to the risk of losing market share. Similarly, the research found that these costs and disclosure, which affects the management of these costs effectively and objectively, are not measured and calculated by many of the industrial companies in Iraq.